A critical review of fracture mechanics as a tool for multiaxial fatigue life prediction of plastics (Fracture and Structural Integrity, 2015)
Plastics belong to the most complex and probably least understood engineering materials of today. Combining the best aspects of design, mechanical properties and manufacturing, the structural integrity of plastics is on par with aluminium and can in some cases even rival those of steels. One of the most important aspects of plastics is the ability to tailor-drive their material properties for a specific purpose or towards a specific strength value. The morphology of plastics is directly dependent on the manufacturing process, e.g. injection moulding, extruding and casting. Plastics contain multiple phases (crystalline, amorphous, oriented), and are in no sense at all isotropic, although integrally deduced mechanical properties may appear to claim the opposite. As such, it becomes obvious that attempting to analyse such materials using conventional material models and explanations of mechanics is an inherently complex task. The static situation alone requires concepts such as creep, relaxation and rate effects to be incorporated on a numerical level. If the load situation changes, such that cyclic loading is acting on the continuum, with the morphology taken into account (without considering the actual geometrical shape), then the result is that of a complex multiaxial fatigue case. Classical theories used for treating fatigue such as SN or eN analysis have proven much less successful for plastics than they have for metals. Fatigue crack propagation using fracture mechanics has seen some success in application, although appropriate crack initiation criteria still need to be established. The physical facts are more than intriguing. For injection moulded parts (being the most common manufacturing process in place), fracture is in most cases seen to initiate from inside the material, unless the surface has been mechanically compromised. This appears to hold true regardless of the load case. In this review, we have scrutinised physically useful methods of crack initiation, as well as the use of fracture mechanics for multiaxial fatigue life prediction of injectionmoulded plastics. Numerical tools have been utilised alongside experimental experience and public domain data to offer what we hope will be a contemporary overview, and offer an outlook for future research into the matter.
Keywords: Plastics